2006
DOI: 10.1158/1078-0432.ccr-06-0929
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bone Metastasis in Prostate Cancer with Endothelin Receptor Antagonists

Abstract: Recent advances in the understanding of prostate cancer biology and its progression to bone metastasis have led to the development of drugs directed against precise molecular alterations in the prostate tumor cell and host cells in the normal bone environment such as osteoclasts and osteoblasts. Endothelins (ETs) and their receptors have emerged as a potential target in prostate cancer bone metastasis. By activating the ET A receptor, ET-1is pathogenically involved in facilitating several aspects of prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 41 publications
2
103
0
1
Order By: Relevance
“…72 Overall, atrasentan was well tolerated and delayed the progression of hormone-refractory prostate cancer in some men. 73 One of the trials reported a separate pharmaco dynamic analysis of biological end points that included changes in bone deposition markers such as total alkaline phosphatase, bone alkaline phosphatase and the bone resorption markers N-telopeptides, C-telopeptides and deoxy pyridinoline. 74 Analysis revealed that mean changes from baseline in total alkaline phosphatase, bone alkaline phosphatase and deoxy pyridinoline were consistently lower in patients receiving 10 mg atrasentan than in patients receiving placebo.…”
Section: Niche Trials: the Bone Metastasis Paradigmmentioning
confidence: 99%
“…72 Overall, atrasentan was well tolerated and delayed the progression of hormone-refractory prostate cancer in some men. 73 One of the trials reported a separate pharmaco dynamic analysis of biological end points that included changes in bone deposition markers such as total alkaline phosphatase, bone alkaline phosphatase and the bone resorption markers N-telopeptides, C-telopeptides and deoxy pyridinoline. 74 Analysis revealed that mean changes from baseline in total alkaline phosphatase, bone alkaline phosphatase and deoxy pyridinoline were consistently lower in patients receiving 10 mg atrasentan than in patients receiving placebo.…”
Section: Niche Trials: the Bone Metastasis Paradigmmentioning
confidence: 99%
“…Accordingly, selective ET A R antagonism inhibits ET-1-mediated induction of MMPs and the uPA/PAI system [2,3,12]. In breast cancer cells, the pro-invasive effect of ET-1 could be a result of interactions between ET A R downstream cascades and HIF-1α signalling: as previously shown in melanoma and ovarian cancer cells, ET-1 via HIF-1α activation induces pro-invasive factors [2,40].…”
Section: Discussionmentioning
confidence: 75%
“…ZD4054 inhibits proliferation of ovarian carcinoma cells and tumour growth in vivo [6], enhances paclitaxel efficacy [10] and exhibits improved antitumoural activity when combined with EGFR inhibitor gefitinib [11]. In prostate cancer, ZD4054 has been evaluated for its efficacy on bone metastases in hormone-refractory prostate cancer (HRPC) [3,12].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelins (ETs) and their receptors have emerged as a potential target in prostate cancer bone metastasis. ET-1 antagonists such as atrasentan (ABT-627) and ZD4054 are currently being clinically evaluated as a biological therapy for prostate cancer bone metastasis [185]. PSK1404, an antagonist of α5β3 integrin significantly inhibits bone metastasis in animal models of metastatic breast and ovarian cancer [186].…”
Section: Therapeuticsmentioning
confidence: 99%